Sources and levels of phosphorus on rangpur lime growing in pots - Nicoli, Amantino Martins; Souza, Maurício de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effect of some P sources and levels on the 'Rangpur' lime (Citrus limonia Osbeck) growing in pots until transplanting time. The experiment was conducted in a greenhouse at the Escola Superior de Agricultura de Lavras, Lavras, MG, Brazil, September 1979 to March 1980. The total of 17 treatments was carried out with six replications, in which ordinary superphosphate (OS), concentrated superphosphate (CS), phosphoric acid (PA) and rock phosphate (RP) were used at four levels: 80, 160, 320 and 1,280 g/m3 of soil. The variables analysed were: plant height, root length top plant dry weight and total dry weight, at six months after planting. The best results for all variables were obtained when 1,280 g of P2O5/m3 of soil was applied for all P sources except for PA. The best results for total dry matter were obtained with the highest levels of CS and OS, which were 21% and 16% higher than RP, respectivelly, when used at the same rate.